HUBUNGAN SOSIAL EKONOMI MASYARAKAT DENGAN KEJADIAN COVID-19 DI KABUPATEN KUDUS - Muhammad Husni Mubaroq; Ervi Rachma Dewi; David Laksamana Caesar (J-KESMAS: Jurnal Kesehatan Masyarakat, 2021)
The coronavirus outbreak has been designated a pandemic, this is due to the extent of its spread and widespread severity. The total global Covid-19 confirmed cases in October 2020 were 42 million cases with a mortality rate of 1 million deaths (CFR 2.7%) in 216 infected countries and 180 local transmission countries. Confirmed cases of Covid-19 in Kudus Regency in October were 131 cases and were included in the orange zone.. The purpose of this study was to determine the relationship between the socio-economic conditions of the community and the incidence of Covid-19 in Kudus Regency. This research is an analytic survey with a case control research design. The study was conducted from April to October 2021. The number of respondents in this study was 100 people with details of 50 positive Covid-19 respondents and 50 COVID-19 risk respondents.